2001
DOI: 10.2355/isijinternational.41.1389
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism and Annealing Behavior of Nanocrystalline Ferrite in Pure Fe Fabricated by Ball Milling.

Abstract: Nanocrystalline ferrite formation by ball milling in pure Fe (0.004 mass% C) has been studied through morphology observation and microhardness measurements. It was found that nano-ferrite first formed at the outer surface area in the powders at the early stage of ball milling, which was attributed to the deformation localization. The boundaries between the nano-ferrite and work-hardened regions are quite clear under SEM and the hardness of nano-ferrite region is more than 3 GPa higher than that of the work-har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
15

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 15 publications
1
62
0
15
Order By: Relevance
“…Such microstructural evolution was observed in the milled powders irrespective of the carbon content (0.004-0.89 mass% C) or starting microstructure (ferrite, martensite, pearlite or spheroidite). [11][12][13][14] It should be noted that there is a drastic difference in hardness between these two types of structures as is shown in Fig. 2(a).…”
Section: Microstructural Evolution Of Specimen Withmentioning
confidence: 99%
See 2 more Smart Citations
“…Such microstructural evolution was observed in the milled powders irrespective of the carbon content (0.004-0.89 mass% C) or starting microstructure (ferrite, martensite, pearlite or spheroidite). [11][12][13][14] It should be noted that there is a drastic difference in hardness between these two types of structures as is shown in Fig. 2(a).…”
Section: Microstructural Evolution Of Specimen Withmentioning
confidence: 99%
“…[11][12][13][14] However, nanocrystallization by ball drop test is limited in high carbon steels (Fe-0.89C with pearlite or spheroidite structure). This reason is considered as follows.…”
Section: Nanocrystallization Of Fe-015c Specimen By Ballmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been generally understood that ball milling gradually refine the grain size to the final nanocrystalline structure. However, our previous works 14,[17][18][19] revealed that nanocrystallization in steels by ball milling is not a gradual process, but there is a sharp transition from work-hardening state to nanocrystalline state.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the formation of nanocrystalline ferrite in Fe-C alloys (including pure iron) by ball milling has been reported. 7,8,[14][15][16][17][18][19] Various mechanisms of nanocrystallization have been proposed by many researchers according to their experimental results. It has been generally understood that ball milling gradually refine the grain size to the final nanocrystalline structure.…”
Section: Introductionmentioning
confidence: 99%